Suicidality among trans people in Ontario: Implications for social work and social justice / La suicidabilité parmi les personnes trans en Ontario : Implications en travail social et en justice sociale - Bauer, Greta; Pyne, Jake; Francino, Matt; Hammond, Rebecca (Service social)

(untitled) (École de service social de l’Université Laval, 2013)
AbstractWhile transgender and transsexual (trans) communities have been documented to experience high rates of suicidality, little attention has been paid to how this may vary based on experiences of social injustice. Using survey data from the Trans PULSE Project (n=433), we estimated that suicidal thoughts were experienced by 36% of trans Ontarians over the past year, and that 10% attempted suicide during that time. Moreover, we documented that youth and those experiencing transphobia and lack of support are at heightened risk. Suicidality varied greatly by medical transition status, with those who were planning to transition sex, but who had not yet begun, being most vulnerable. Recommendations are made for improving wellbeing in trans communities, through policy advocacy, service provision, access to transition care, and fostering accepting families and communities.